2012
DOI: 10.1007/s00122-012-1799-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying quantitative trait loci and determining closely related stalk traits for rind penetrometer resistance in a high-oil maize population

Abstract: Stalk lodging in maize causes annual yield losses between 5 and 20% worldwide. Many studies have indicated that maize stalk strength significantly negatively correlates with lodging observed in the field. Rind penetrometer resistance (RPR) measurements can be used to effectively evaluate maize stalk strength, but little is known about the genetic basis of this parameter. The objective of this study was to explore a genetic model and detect quantitative trait loci (QTL) of RPR and determine relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
67
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 16 publications
11
67
2
Order By: Relevance
“…The broad-sense heritability of RPR in maize, estimated in two previous studies as well as our study, reached over 90% in some segregating populations [2,17]. The high broad-sense heritability reflects the accuracy and feasibility of the method used to quantify RPR in these studies.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The broad-sense heritability of RPR in maize, estimated in two previous studies as well as our study, reached over 90% in some segregating populations [2,17]. The high broad-sense heritability reflects the accuracy and feasibility of the method used to quantify RPR in these studies.…”
Section: Discussionsupporting
confidence: 72%
“…Among these QTL, only the largest-effect QTL, qRPR3-1 , was also identified in two previous studies by Flint-Garcia et al [2] and Hu et al [17]; qRPR3-2 and qRPR6-2 were also detected in the Flint-Garcia et al study and were found to explain 6.7% and 13.8% of the phenotypic variation, respectively [2]. Our study revealed that a few large-effect QTL, together with some minor-effect QTL, provide most of the genetic basis of RPR, consistent with previous studies [2,17,18]. Together with this study, a total of 69 RPR-associated QTL have been identified in 33 segregating populations.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although the content of cellulose or lignin is related to stem rigidity (Taylor et al, 1999;Jones et al, 2001), the relationship between cellulose or lignin content and lodging resistance has not been clear. Stalk strength in previous work with maize significantly negatively correlates with lodging observed in the field (Hu et al, 2012). Application of abundant nitrogen at the ripening stage increases the accumulation of carbohydrates in stems and improves lodging resistance, but it also reduces cellulose content (Matsuzaki et al, 1972).…”
Section: Resultsmentioning
confidence: 90%